Inside the Scriptorium: Non-Invasive In Situ Identification of Dyes in Illuminated Manuscripts by Microspectrofluorimetry and Multivariate Analysis: The Crescenzago Choir Books (End 15th Century) as a Case Study - Margherita Longoni; Noemi Hopes; Federico Rossi; Miriam Rita Tessera; Marco Petoletti; Silvia Bruni (Heritage, 2023)
In the present work, a method is proposed that combines spectrofluorimetry with multivariate analysis (cluster and principal components) to non-invasively investigate natural dyes used, mainly in the form of lakes, in illuminations. First, a consistent number of mock-up samples of red and purple lakes (from brazilwood, madder, kermes, cochineal, lac dye, folium and orcein) were prepared following the recipes reported in ancient treatises, then the experimental conditions for their non-invasive investigation were optimized by benchtop instrumentation and transferred to a portable microprobe suitable for in situ analyses. For all the coloring materials examined, it was thus possible to obtain a satisfactory grouping of samples containing the same dye. The analytical protocol was finally extended to the characterization of dyes in the Crescenzago choir books, illuminated manuscripts dating back to the end of the 15th century.